Evolution of Knowledge, Awareness, and Practices regarding Zika Virus from 2016 to 2017 - Quinton Katler; Prachi Godiwala; Charles Macri; Beth Pineles; Gary Simon; Aileen Chang; Homa Ahmadzia (Hindawi Limited, 2017)
Objective. Our team created a knowledge, attitudes, and practice (KAP) survey in order to assess changes over time in healthcare provider and community member awareness of Zika virus symptoms, transmission, treatment, and current and future concerns. Study Design. The cross-sectional survey was issued at an academic medical center in Washington, DC, and via an online link to healthcare providers and community members between June and August 2016. Survey distribution was then repeated the following year, from March to April 2017. Outcomes were compared by survey year and healthcare provider versus community member status using SAS Program Version 9.4. Results. Significant differences in knowledge, attitudes, and practices existed between 2016 and 2017 survey time points. By 2017, more respondents had knowledge of various Zika virus infection characteristics; however healthcare provider knowledge also waned in certain areas. Attitudes towards Zika virus infection displayed an overall decreased concern by 2017. Practice trends by 2017 demonstrated fewer travel restrictions to Zika-endemic areas and increased mosquito protective measures within the US. Conclusions. Our results provide novel insight into the transformation of knowledge, attitudes, and practice of community members and healthcare providers regarding Zika virus since its declaration as a public health emergency of international concern in 2016.